A novel corpus of naturalistic picture book reading with 2-to-3 year old children - Anastasia Stoops; Jessica L Montag (Language Development Research)
Substantial literature suggests that reading to children is positively associated with language outcomes, but the causal pathways are less well understood. One possibility is that reading to children promotes language input that is particularly useful for some aspects of language learning. To better understand the language that is produced during picture book reading, we built a sharable corpus of caregiver-child interactions during book reading recorded in homes. Caregivers overwhelmingly read the book text. However, books varied in the language they generated, with some books promoting more conversational turns and extra-textual language, while others promoted more overall words, unique words, and longer utterances. Relative to other conversational contexts, books generally generated overall more words, more lexically diverse talk, and longer utterances. We see different profiles of language generated during book reading that are all plausibly linked with language skills. If a causal pathway exists between shared book reading and language outcomes, a sensible candidate may be that reading provides a varied range of linguistic experiences.